PKM Solialisasi dan Pengembangan Olahraga Petanque Kabupaten Jeneponto - Andi Amry Yahya; haeril haeril (Universitas PGRI Semarang, 2021)
In sports, every sports agents are required to give their best appearance. It is not easily for the untrained, even the well-trained sports agents often have difficulty. The FOPI Jeneponto district has been existed but it still has a little obstacles at training and development. This is because the lack of human resources with the ability to conduct training and development. Therefore, the teams want to do the activity of Sosialization and Development of Petanque Sport of Jeneponto District. The methods of implementation used in this activity are survey, counseling about facilities of petanque, equipment preparation, preparation of training, conducting training program, evaluation about the program and the sustainability of program. The result of this activity structurally for FOPI, the community and athletes who participated very enthusiastic and there is an increase in the ability both physically and technique.